Laser cladding process and strengthening method for polysilicon regulating valve seat

Through the laser cladding process of polysilicon regulating valve seat, including pretreatment, alloy powder preparation, laser cladding and gradient heat treatment, the failure problems of traditional valve seats under high temperature, strong corrosion and wear conditions are solved, and the effects of high corrosion resistance, wear resistance and long service life are achieved.

CN119753674AInactive Publication Date: 2025-04-04KAIRUITE VALVE

Patent Information

Application Number
CN202510259657.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-06
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The seat of the traditional polysilicon spherical regulating valve is prone to surface corrosion and wear failure under high temperature, strong corrosion or polysilicon particle erosion conditions, and the lack of interface bonding strength of the laser cladding layer leads to thermal stress cracking.

Method used

The laser cladding process of polysilicon regulating valve seat is adopted, including valve seat pretreatment, alloy powder preparation, laser cladding, gradient heat treatment and finishing. Specific steps include ultrasonic cleaning and alumina sand blasting treatment, alloy powder composition optimization and ball milling process, laser cladding parameter optimization, segmented tempering and oil quenching treatment, diamond grinding wheel grinding and chemical mechanical polishing.

Benefits of technology

It significantly improves the valve seat's strong corrosion resistance and high wear resistance, extends its service life, and solves the problems of surface corrosion, wear and thermal stress cracking in traditional processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753674A_ABST
    Figure CN119753674A_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of valve seat grinding and polishing technology, and in particular to a laser cladding process and strengthening method for a polysilicon regulating valve seat. The processing technology includes valve seat pretreatment, alloy powder preparation, laser cladding, gradient heat treatment and finishing. Pretreatment improves surface roughness through ultrasonic cleaning, chemical degreasing and sandblasting to facilitate subsequent processing. The alloy powder is specifically proportioned and ball milled to ensure quality. Laser cladding uses a specific laser and parameters for multi-layer cladding. Gradient heat treatment effectively controls stress and strengthens interface bonding. Finishing makes the surface roughness meet the standard. The surface strengthening method covers laser cladding processing, internal defect detection, performance detection and grading, repair and re-inspection, and there is also a passivation treatment process when the corrosion detection does not meet the standard. The present invention has the advantages of strong corrosion resistance, high wear resistance, high process precision and long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of valve seat grinding and polishing technology, in particular to a laser cladding process and a strengthening method for a polysilicon regulating valve seat. Background Art

[0002] In the polysilicon production process, polysilicon ball control valves, as key components, need to frequently deal with harsh working conditions containing granular media such as silicon powder and coal ash. The valve seats of traditional polysilicon ball control valves are easy to wear due to the high hardness and strong scouring properties of silicon powder, which leads to the degradation of valve sealing performance and frequent leakage, seriously affecting production efficiency and stability. At the same time, the chemical substances in the polysilicon production environment are also easy to corrode the valve seats, further shortening their service life.

[0003] After extensive searching, the publication number CN105525288B discloses a method for preparing a reinforced ball valve seat, comprising the following steps: turning a trapezoidal ring groove with a depth of 2 mm on the sealing surface of the ball valve seat after rough machining; pretreating the surface of the ball valve seat; performing nondestructive testing on the sealing surface of the valve seat, etc. The preparation method in the existing technology can reduce the production cost of the enterprise and significantly improve the service life of the ball valve seat when used.

[0004] However, the above preparation method still has the problems of insufficient corrosion resistance of the alloy and limited wear resistance of the cladding layer. These problems will cause the valve seat to be prone to surface corrosion and wear failure under high temperature, strong corrosion or polysilicon particle scouring conditions. Therefore, a laser cladding process and strengthening method for the seat of a polysilicon regulating valve is proposed to solve the above problems. Summary of the invention

[0005] The purpose of the present invention is to provide a laser cladding process and strengthening method for a polysilicon regulating valve seat, which has the advantages of strong corrosion resistance, high wear resistance, high process precision and long service life, and can effectively solve the problems of traditional ball valve seats being easily corroded and failed in high-temperature fluorine-containing or nitric acid media, rapid wear and peeling of the surface under erosion by polysilicon particles, and thermal stress cracking caused by insufficient interface bonding strength of the laser cladding layer.

[0006] To achieve the above object, the present invention provides the following technical solution: a laser cladding process for a polysilicon regulating valve seat, comprising the following steps: Valve seat pretreatment: After using ultrasonic cleaning combined with chemical degreasing agent to remove surface oil and impurities, use aluminum oxide sand with a particle size of 0.5mm to 1mm for sandblasting to make the surface roughness reach Ra12.5μm to Ra25μm; Preparation of alloy powder: In terms of mass percentage, the alloy powder composition is 20% to 25% chromium, 10% to 15% nickel, 15% to 20% tungsten carbide particles, 3% to 5% molybdenum, 0.5% to 1% cerium, and the balance is iron; the powder particle size is controlled at 50 μm to 100 μm by a planetary ball mill, the ball milling time is 4 h to 6 h, and the ball-to-material ratio is 5:1 to 8:1; Laser cladding: using fundamental mode or low-order mode fiber laser, beam quality factor M²≤1.3, with coaxial powder feeder, multi-layer cladding on the valve seat sealing surface, laser power 1500W to 2500W, scanning speed 80mm / min to 120mm / min, spot diameter 3mm to 4mm, overlap rate 50% to 60%, each layer cladding thickness 0.3mm to 0.5mm, powder feeding amount 30g / min to 50g / min; Gradient heat treatment: Stress relief annealing: According to the heat treatment characteristic curve of the alloy material and combined with actual production experience, it is determined that keeping the temperature within the range of 550℃ to 650℃ for 2h to 3h can effectively release the internal stress of the cladding layer and avoid the degradation of material properties caused by excessive annealing; Argon protection: gas flow rate 5L / min to 10L / min, heating rate 5℃ / min to 10℃ / min, cooling rate 3°C / min to 5°C / min; Oil quenching: After keeping at 850℃ to 950℃, immerse in 40℃ to 60℃ rapid quenching oil; Staged tempering: the first stage is 200℃ to 250℃ for 1h to 1.5h, the second stage is 250℃ to 300℃ for 1h to 1.5h; Finishing: Diamond grinding wheel grinding, grinding wheel linear speed 20m / s to 30m / s, feed rate 0.01mm / r to 0.03mm / r, chemical mechanical polishing liquid polishing, polishing liquid pH value 8 to 10, pressure 0.1MPa to 0.3MPa, so that the surface roughness reaches Ra0.2μm to Ra0.4μm.

[0007] Preferably, the tungsten carbide particles are spherical with an average particle size of 10 μm to 20 μm, and are uniformly dispersed in the matrix alloy by a planetary ball mill. The ball milling energy density is 0.8 J / g to 1.2 J / g, wherein the ball milling energy density is calculated by the formula E=0.5·m·v² / t, where m is the mass of the grinding ball, v is the linear velocity, and t is the time.

[0008] When using the above technical solution, the ball milling process parameters of tungsten carbide particles are optimized to ensure that they are evenly dispersed in the matrix alloy. This control method improves the overall hardness and wear resistance of the cladding layer, while avoiding local stress concentration caused by particle agglomeration, making the material performance more stable and reliable.

[0009] Preferably, in the laser cladding, the laser focus position is controlled to be 0.2 mm to 0.5 mm above the valve seat surface, and the molten pool Marangoni number is less than or equal to -0.5, wherein the Marangoni number is calculated by the formula Ma=Δγ·L / μ·κ, Δγ is the surface tension gradient of the molten pool, L is the characteristic length of the molten pool, μ is the melt viscosity, κ is the thermal diffusivity, and μ and κ are in a multiplication relationship.

[0010] When the above technical solution is adopted, the melt splash and defect formation during the cladding process can be effectively suppressed by accurately adjusting the laser focus position and the flow characteristics of the molten pool. This control method enhances the density of the cladding layer, reduces the generation of pores and cracks, and ensures that the surface quality meets the requirements of high-precision working conditions.

[0011] Preferably, the residual stress of the cladding layer after the segmented tempering is ≤200 MPa, and the interface bonding strength between the tungsten carbide particles and the substrate is ≥350 MPa.

[0012] When the above technical solution is adopted, the internal stress of the cladding layer is gradually released by adopting the segmented tempering process, which significantly reduces the residual stress level and strengthens the bonding strength of the interface between tungsten carbide and the substrate. This method improves the material's fatigue resistance and impact resistance under complex working conditions.

[0013] Preferably, the planetary ball mill uses zirconium oxide grinding balls with a grinding ball diameter of 5 mm to 10 mm, the inner wall of the ball mill is lined with polyurethane, and the rotation speed is 200 r / min to 300 r / min.

[0014] When using the above technical solution, by selecting grinding balls and linings of specific materials and controlling the ball mill speed, powder contamination is reduced and particle morphology is improved. This process optimization ensures the fluidity and uniformity of the alloy powder, providing high-quality raw materials for the subsequent cladding process.

[0015] Preferably, in the alloy powder, the cerium element inhibits oxidation of tungsten carbide through grain boundary segregation, and the cerium concentration at the grain boundary is more than 5 times that of the matrix, as measured by EDS spectrum.

[0016] When using the above technical solution, the grain boundary segregation characteristics of cerium, a rare earth element, are used to inhibit the oxidation reaction of tungsten carbide during high-temperature processing. This technical means not only protects the integrity of the hard particles, but also refines the matrix grains, further improving the corrosion resistance and high-temperature stability of the material.

[0017] The method for strengthening the valve seat of a polysilicon regulating valve further includes the following steps: Step 1: Laser cladding processing: The above process is used to laser clad the valve seat sealing surface and easily worn parts to form a composite strengthening layer with a thickness of 0.9mm to 2.5mm; the molten pool morphology is monitored in real time during the cladding process to ensure that the molten pool width is 1.2 to 1.5 times the spot diameter, and there is no spatter or pores on the surface of the cladding layer; Step 2: Internal defect detection: Use ultrasonic flaw detection equipment with a frequency of 2MHz to 5MHz to scan the entire area of ​​the cladding layer. The flaw detection sensitivity is set to the base sensitivity plus 6dB, and the scanning speed is 50mm / s to 80mm / s. If the defect reflection amplitude detected exceeds 50% of the base amplitude and the defect size is greater than 0.1mm, it is judged as unqualified; Step 3: Performance testing and grading: Hardness test: carried out at room temperature of 20℃±2℃ and relative humidity of 60%±5%. Five test points are evenly selected along the circumference of the cladding layer surface and measured using a Rockwell hardness tester. The surface hardness is required to be HRC55 to HRC60, and the hardness difference between adjacent test points is ≤HRC2. The test is conducted every 0.2mm in the depth direction of the section, and the gradient difference is ≤HRC5. Wear test: It is carried out in a dust-free, constant temperature and humidity laboratory environment, using a pin-on-disc friction and wear tester. The wear pin is made of tungsten carbide, with a hardness of ≥HRA85 and an end surface roughness of Ra0.1μm to Ra0.2μm. The test conditions are a load of 20N to 30N, a rotation speed of 200rpm to 300rpm, and a time of 1h to 2h. After the test, the wear amount is weighed. If it is greater than 0.05g or a continuous peeling band appears on the surface, it is judged as unqualified. Corrosion test: It was carried out in a well-ventilated chemical laboratory. A corrosion solution containing 10% to 15% hydrofluoric acid and 5% to 10% nitric acid was prepared at a temperature of 25°C ± 1°C. After the sample was immersed for 24 hours, the polarization curve was tested using an electrochemical workstation at a scanning rate of 0.5mV / s to 1mV / s. The self-corrosion current density was >1×10 -6 A / cm² is considered unqualified; Step 4: Repair and re-inspection: The unqualified valve seat is partially laser remelted and repaired, and the repair area covers the 1mm to 2mm range around the defect. After repair, it is ground flat using a diamond grinding wheel at a linear speed of 15m / s to 20m / s, and steps two and three are repeated; if the valve seat still fails after three re-inspections, it is deemed scrapped.

[0018] Preferably, the local laser remelting repair parameters in step 4 are: The laser power is 1200W to 1800W, and the power density is a function of the thickness of the repair area, satisfying the formula: Power density = repair thickness × (500W / mm² to 800W / mm²); The scanning speed is 60mm / min to 100mm / min, and the ratio to the original cladding speed is ≤0.8; The powder feeding rate is 20g / min to 40g / min, and the powder composition is 80% to 120% of the original alloy powder.

[0019] When using the above technical solution, the local repair process of the defective area is carried out by dynamically adjusting the laser parameters and powder feeding strategy to achieve the performance matching between the repaired area and the original cladding layer. This precise repair technology reduces material waste and avoids secondary damage caused by over-processing.

[0020] Preferably, in the wear detection of step three, the contact area between the tungsten carbide pin and the valve seat is 5mm² to 10mm², and the contact pressure between the pin end face and the surface of the cladding layer is 0.5MPa to 1.0MPa; the friction coefficient is collected every 15 minutes during the test. If the friction coefficient fluctuates by more than 0.2 or a sudden change occurs, it is determined that the cladding layer has uneven defects.

[0021] When the above technical solution is adopted, in the wear detection, the potential uneven composition or bonding defects in the cladding layer can be quickly identified by monitoring the dynamic changes of the friction coefficient. This method can provide early warning of material failure risks and provide real-time feedback for process improvement.

[0022] Preferably, if the corrosion detection result of step 3 does not meet the requirements, the following passivation treatment process is adopted: Pretreatment: immerse the valve seat in a nitric acid solution with a mass fraction of 5% to 10%, and ultrasonically clean it for 10 to 20 minutes; Passivation: Soak in a nitric acid solution at 40°C to 50°C and with a mass fraction of 5% to 10% for 10 to 20 minutes; Post-treatment: rinse with deionized water, dry, and keep at 200℃ to 250℃ for 0.5h to 1h; Retest: After passivation, retest the corrosion test. The self-corrosion current density must be ≤1×10 -6 A / cm².

[0023] When the above technical solution is adopted, a passivation treatment process is used to form a dense oxide film on the surface of the cladding layer, which significantly improves the corrosion resistance of the material in strong acid media. This post-treatment technology makes up for the protection shortcomings of the cladding layer in extreme chemical environments and extends the service life of the valve seat.

[0024] Compared with the prior art, the present invention has the following beneficial effects: 1. Significantly improved corrosion resistance and wear resistance: 1. Through the specific alloy ratio of 20% to 25% chromium content, 10% to 15% nickel, and 15% to 20% tungsten carbide particles, combined with the segmented tempering process, the surface hardness of the cladding layer can be stably reached HRC55 to HRC60, and the wear resistance is more than 3 times higher than that of the traditional valve seat. During the laser cladding process, a fundamental mode or low-order mode fiber laser is used with a spot diameter of 3mm to 4mm and an overlap rate of 50% to 60% to ensure that the tungsten carbide particles are evenly distributed and effectively resist the erosion of polysilicon particles.

[0025] 2. Through stress relief annealing at 550℃ to 650℃ and oil quenching at 850℃ to 950℃, the residual stress of the cladding layer was effectively reduced to below 200MPa. Subsequently, diamond wheel grinding and chemical mechanical polishing were used to further reduce the surface roughness to Ra0.2μm to Ra0.4μm, significantly reducing the risk of adhesion of corrosive media.

[0026] 2. Breakthrough improvement in process precision and quality stability: 1. The laser focus adjustment system is used to control the laser focus position at 0.2mm to 0.5mm above the valve seat surface. Combined with the coordinated control of the scanning speed of 80mm / min to 120mm / min and the powder feeding amount of 30g / min to 50g / min, the thickness error of each layer of cladding is less than ±0.05mm, and the uniformity of the total thickness of the cladding layer of 0.9mm to 2.5mm reaches more than 98%.

[0027] 2. Through full-area scanning with 2MHz to 5MHz ultrasonic flaw detection equipment, with the benchmark sensitivity plus 6dB detection standard, 100% detection of defects larger than 0.1mm can be achieved. Combined with the local laser remelting repair process, the repair parameters include laser power of 1200W to 1800W and scanning speed of 60mm / min to 100mm / min. The scrap rate is reduced from 15% of the traditional process to less than 2%.

[0028] 3. Full-process quality closed-loop control system: Set up three standards for hardness testing, wear testing and corrosion testing: surface hardness HRC55 to HRC60, and the hardness difference between adjacent test points ≤ HRC2; wear amount ≤ 0.05g; self-corrosion current density ≤ 1×10 -6 A / cm². These standards ensure the consistency of product performance.

[0029] 2. During laser remelting repair, the power density is dynamically adjusted to the thickness of the cladding layer in the repair area × 500W / mm² to 800W / mm², and the ratio of the scanning speed to the original cladding speed is ≤0.8. In this way, the hardness difference between the repair area and the substrate is controlled to ≤HRC2, avoiding secondary damage caused by the repair process.

[0030] 4. Long-term stability of surface strengthening layer: 1. Alumina sandblasting pretreatment makes the surface roughness reach Ra12.5μm to Ra25μm, significantly enhancing the bonding strength of the cladding layer by more than 30%; corrosion detection uses a solution containing 10% to 15% hydrofluoric acid and 5% to 10% nitric acid, immersed in 25℃±1℃ for 24 hours to ensure that the service life of the cladding layer in a strong acid environment exceeds 3 years.

[0031] 2. During the finishing stage, the grinding wheel linear speed is controlled at 20m / s to 30m / s, and the polishing liquid pressure is controlled at 0.1MPa to 0.3MPa. Through precise matching, the surface density reaches 99.5% and the porosity is less than 0.3%. These measures completely solve the problem of early failure caused by surface defects in traditional processes.

[0032] Core comparison of technical effects: Performance Indicators Traditional crafts The present invention Surface hardness (HRC) 45-50 55-60 Wear amount (2h test) 0.15-0.25g ≤0.05g Corrosion current density <![CDATA[5×10 -6 A / cm²]]> <![CDATA[≤1×10 -6 A / cm² <!-- 4 -->]]> Porosity of cladding layer 3-5% <0.5% This technical solution systematically solves the failure problem of polysilicon valve seats under strong corrosion and high wear conditions through alloy composition optimization, laser cladding parameter control and gradient heat treatment, working in synergy with defect detection, repair and performance grading systems, achieving a technical leap in extending service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is the full process diagram of the present invention; Figure 2 This is a process flow chart of the valve seat pretreatment process of the present invention; Figure 3 It is a process parameter diagram for preparing alloy powder of the present invention; Figure 4 It is a relationship diagram of laser cladding process parameters of the present invention; Figure 5 It is a process step diagram of gradient heat treatment of the present invention; Figure 6 This is a flow chart of the valve seat surface strengthening method of the present invention; Figure 7 is a relationship diagram of wear detection parameters of the present invention; Figure 8 It is a process flow chart of the passivation treatment of the present invention. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Example 1: Valve seat pretreatment of polysilicon regulating valve seat by laser cladding process In order to achieve effective pretreatment of the polysilicon spherical regulating valve seat to meet the requirements of subsequent laser cladding, such as Figure 1 and Figure 2 , an embodiment provided by the present invention: 1. Overall technological status exist Figure 1 In the process of valve seat pretreatment, valve seat pretreatment is the initial and key link. Its quality directly affects the bonding effect between the subsequent laser cladding layer and the valve seat substrate, and thus affects the performance of the entire valve seat.

[0036] 2. Specific process of pretreatment 1. Cleaning process Ultrasonic cleaning combined with chemical degreasing agents are used to remove surface oil and impurities. The ultrasonic cleaning frequency is 40kHz and the time is 15 minutes; the chemical degreasing agent mainly contains surfactants and emulsifiers, which reduce the adhesion between oil and the valve seat surface through emulsification and dispersion, and further clean for 10 minutes. From the principle of ultrasonic cavitation effect in physics, it can be known that when ultrasonic waves propagate in liquids, their frequency is usually above 20kHz. This high-frequency vibration causes tiny bubbles to form inside the liquid. When the bubbles close, a momentary high pressure is generated, and the pressure can reach hundreds of atmospheres. Such a strong impact force can effectively peel off oil and impurities from the valve seat surface.

[0037] 2. Sand blasting Subsequently, alumina sand particles with a particle size of 0.5mm to 1mm are used for sandblasting. The sandblasting pressure is controlled at 0.4MPa to 0.6MPa, and the sandblasting time is 10 minutes. From the perspective of material science, during the sandblasting process, the high-speed sprayed alumina sand particles hit the surface of the valve seat, causing it to form tiny bumps and bumps. According to the surface roughness evaluation standard, this treatment method makes the surface roughness reach Ra12.5μm to Ra25μm. A larger surface roughness can increase the contact area between the subsequent laser cladding layer and the valve seat substrate. According to the mechanical bonding theory, the increase in contact area can significantly increase the bonding force between the two, laying the foundation for the subsequent laser cladding process to proceed smoothly and form a solid cladding layer.

[0038] Example 2: Preparation of alloy powder by laser cladding process for polysilicon regulating valve seat In order to prepare high-quality alloy powder suitable for laser cladding of polycrystalline silicon spherical regulating valve seats, Figure 1 and Figure 3 , an embodiment provided by the present invention: 1. Role in the overall process exist Figure 1In the process of laser cladding, alloy powder preparation is an important part. Its preparation quality directly affects the performance of the laser cladding layer, which in turn determines the performance of the valve seat in actual use, such as wear resistance, corrosion resistance and other key properties.

[0039] 2. Alloy Powder Preparation Process 1. Ingredient design In terms of mass percentage, the alloy powder composition is 20% to 25% chromium, 10% to 15% nickel, 15% to 20% tungsten carbide particles, 3% to 5% molybdenum, 0.5% to 1% cerium, and the balance is iron. From a chemical perspective, chromium plays a vital role in the alloy. When the alloy is exposed to air or corrosive media, chromium reacts with oxygen to form a dense chromium oxide film on the surface of the alloy. This oxide film has good chemical stability and density, and can effectively prevent the corrosive medium from further eroding the interior of the alloy. The atomic radius of nickel is similar to that of iron, and it can form a solid solution in the alloy. Through the solid solution strengthening mechanism, the toughness and strength of the alloy are enhanced, and the comprehensive properties of the alloy are improved, making it less prone to brittle fracture when subjected to external forces. Tungsten carbide particles have extremely high hardness, usually up to 2000-3000HV, which plays a role of dispersion strengthening in the alloy, significantly improving the wear resistance of the alloy, just like adding steel bars to concrete, which enhances the overall strength and wear resistance. Molybdenum can improve the high-temperature strength of the alloy. In a high-temperature environment, molybdenum atoms can hinder the movement of dislocations, thereby improving the alloy's ability to resist deformation. At the same time, molybdenum can also enhance the alloy's ability to resist chemical corrosion in the polysilicon production environment, especially for some corrosive media such as sulfur and chlorine. Cerium, as a rare earth element, has the characteristic of segregation at the grain boundary according to the grain boundary theory of materials science. During high-temperature processing, cerium can inhibit the oxidation of tungsten carbide. According to EDS energy spectrum measurement, the cerium concentration at the grain boundary is more than 5 times that of the matrix. This grain boundary segregation not only protects the integrity of the tungsten carbide hard particles, but also refines the matrix grains, making the alloy's organizational structure more uniform, thereby further improving the corrosion resistance and high-temperature stability of the material.

[0040] 2. Ball milling process The powder particle size is controlled at 50μm to 100μm by a planetary ball mill, the ball milling time is 4h to 6h, and the ball-to-material ratio is 5:1 to 8:1. The planetary ball mill uses zirconium oxide grinding balls with a diameter of 5mm to 10mm, a polyurethane lining on the inner wall of the ball milling jar, and a rotation speed of 200r / min to 300r / min. From the perspective of material processing, zirconium oxide grinding balls have high hardness and wear resistance, and are not easy to wear themselves during the ball milling process, thereby reducing the pollution of the alloy powder. The polyurethane lining has good elasticity and wear resistance, which can reduce the noise generated by the collision between the grinding balls and the inner wall of the ball milling jar, and can also reduce the adhesion of the powder during the ball milling process, which is conducive to improving the ball milling efficiency. During the ball milling process, the grinding balls impact, grind and stir the alloy powder under the action of centrifugal force, revolution and rotation. Appropriate ball milling time, ball-to-material ratio and speed setting can fully refine the alloy powder particles and mix them evenly. By controlling the ball milling energy density, for example, for the ball milling of tungsten carbide particles, the energy density is 0.8J / g to 1.2J / g, and the ball milling energy density is calculated by the formula E=0.5·m·v² / t, where m is the mass of the grinding ball, v is the linear velocity, and t is the time. This ensures that the tungsten carbide particles can be evenly dispersed in the matrix alloy, avoiding local stress concentration caused by particle agglomeration, and ensuring that the alloy powder has good fluidity and uniformity, providing high-quality raw materials for subsequent high-quality laser cladding, and closely connecting the subsequent links of the laser cladding process.

[0041] Example 3: Laser cladding processing and preliminary testing of polysilicon regulating valve seat strengthening method In order to effectively strengthen the surface of the polysilicon spherical regulating valve seat, a high-quality composite strengthening layer is formed by laser cladding processing and preliminary quality control is performed, such as Figure 1 and Figure 6 , an embodiment provided by the present invention: 1. Key position in surface strengthening methods exist Figure 1 In the process of laser cladding, laser cladding is one of the core steps, and its quality is directly related to the effect of valve seat surface strengthening. Preliminary inspection is an important means to ensure the quality of laser cladding, and the two together lay the foundation for subsequent processing links.

[0042] 2. Laser cladding processing and preliminary testing process 1. Laser cladding processing First, a specific process is used to laser clad the valve seat sealing surface and easily worn parts, aiming to form a composite strengthening layer with a thickness of 0.9mm to 2.5mm. A fundamental mode or low-order mode fiber laser is used, with a beam quality factor of M²≤1.3, a laser power of 1500W to 2500W, a scanning speed of 80mm / min to 120mm / min, and a spot diameter of 3mm to 4mm. This high-quality laser beam can ensure a more uniform energy distribution, which is conducive to the precise control of the cladding process. With a coaxial powder feeder, the powder feeding amount is 30g / min to 50g / min, which can evenly feed the alloy powder into the molten pool. During the cladding process, the molten pool morphology is monitored in real time through high-speed camera technology such as a high-speed camera with a frame rate of 10,000fps to ensure that the molten pool width is 1.2 to 1.5 times the spot diameter, and there is no spatter or pores on the surface of the cladding layer. If abnormal fluctuations, spatter or pores are found in the molten pool, the laser power, scanning speed or powder feeding amount can be adjusted immediately to ensure the quality of the cladding layer. Based on the quality control principle of material forming, the reasonable proportional relationship between the width of the molten pool and the spot diameter can ensure the effective use of laser energy and the uniformity of the cladding layer. If the width of the molten pool is too small, the alloy powder may not be fully melted and fused; if the width of the molten pool is too large, it may cause energy waste and unstable quality of the cladding layer. Real-time monitoring of the molten pool morphology can promptly detect and correct problems in the cladding process. For example, through technical means such as high-speed photography, once abnormal fluctuations, spatter or pores in the molten pool are found, the laser power, scanning speed, powder feeding amount and other parameters can be adjusted immediately to ensure the quality of the cladding layer.

[0043] 2. Internal defect detection After the laser cladding process is completed, internal defect detection is carried out immediately. The cladding layer is scanned in the entire area using an ultrasonic flaw detection device with a frequency of 2MHz to 5MHz. The flaw detection sensitivity is set to the base sensitivity plus 6dB. The base sensitivity is pre-calibrated according to the material and thickness of the cladding layer, and the scanning speed is 50mm / s to 80mm / s. According to the principle of ultrasonic flaw detection, when ultrasonic waves propagate in the cladding layer, reflection, refraction and scattering will occur when encountering defects. The setting of flaw detection sensitivity determines the minimum size and nature of defects that can be detected. Setting the flaw detection sensitivity to the base sensitivity plus 6dB can improve the detection capability of tiny defects. Reasonable control of the scanning speed can not only ensure the comprehensiveness of the detection, but also improve the detection efficiency. If the defect reflection amplitude is detected to exceed 50% of the base amplitude and the defect size is greater than 0.1mm, it is judged as unqualified. This laser cladding process and preliminary detection link plays a key quality assurance role in the entire surface strengthening method, laying the foundation for subsequent performance testing and grading as well as possible repair work.

[0044] Example 4: Performance testing, repair and passivation treatment of polysilicon control valve seat strengthening method In order to comprehensively evaluate the surface strengthening effect of polysilicon ball control valve seats, effectively repair unqualified products, and take remedial measures for corrosion problems, such as Figure 1 , Figure 6 , Figure 7 and Figure 8 , an embodiment provided by the present invention: 1. Role in the overall process of surface strengthening exist Figure 1 In the process of valve seat inspection, performance testing, repair and passivation treatment are important links to ensure the quality and performance of valve seats. They together constitute a closed-loop quality control system. Through the quality monitoring and feedback mechanism of the whole process, the quality and service life of valve seats are comprehensively improved.

[0045] 2. Performance testing, repair and passivation process 1. Performance testing Hardness test: Use Rockwell hardness tester to select 5 test points evenly along the circumference of the cladding layer surface, and measure once every 0.2mm in the depth direction of the section. The surface hardness is required to be HRC55 to HRC60, the hardness difference between adjacent test points is ≤HRC2, and the gradient difference is ≤HRC5. This can fully reflect the uniformity of the hardness of the cladding layer. The small hardness difference between adjacent test points and the gradient difference in the depth direction of the section indicate that the hardness distribution of the cladding layer is uniform, and there is no obvious hardness mutation area, which ensures the consistency of the wear resistance of the valve seat in different parts.

[0046] Wear detection: A pin-on-disc friction and wear tester is used. The wear pin is made of tungsten carbide, with a hardness of ≥HRA85 and an end surface roughness of Ra0.1μm to Ra0.2μm. The test conditions are a load of 20N to 30N, a speed of 200rpm to 300rpm, and a time of 1h to 2h. After the test, the wear amount is weighed. If it is >0.05g or a continuous peeling band appears on the surface, it is judged as unqualified. The relationship between the relevant parameters can be referred to Figure 7 . The wear pin made of tungsten carbide has high hardness and wear resistance, and can simulate the wear of polysilicon particles on the valve seat surface. By controlling the test conditions, such as load, speed and time, the wear resistance of the cladding layer can be evaluated more accurately. During the test, the friction coefficient is collected every 15 minutes. If the friction coefficient fluctuates by more than 0.2 or a sudden change occurs, it is determined that the cladding layer has uneven defects. The stability of the friction coefficient can reflect the uniformity and integrity of the surface of the cladding layer. Excessive fluctuations or sudden changes may mean that the cladding layer has problems such as uneven composition and poor bonding.

[0047] Corrosion test: Prepare a corrosion solution containing 10% to 15% hydrofluoric acid and 5% to 10% nitric acid by mass, and the solution temperature is 25℃±1℃; after soaking the sample for 24h, use an electrochemical workstation to test the polarization curve at a scanning rate of 0.5mV / s to 1mV / s, and the self-corrosion current density is >1×10 -6 A / cm² is considered unqualified. The polysilicon production environment often contains highly corrosive media such as hydrofluoric acid and nitric acid. By simulating this corrosive environment, the corrosion resistance of the cladding layer under actual working conditions can be tested. The polarization curve can reflect the electrochemical behavior of the material during the corrosion process. The smaller the self-corrosion current density, the better the corrosion resistance of the material.

[0048] 2. Repair phase For unqualified valve seats, local laser remelting repair is performed, and the repair area covers the range of 1mm to 2mm around the defect. The repair parameters are as follows: Laser power: 1200W to 1800W Power density: Repair thickness × (500W / mm² to 800W / mm²) Scanning speed: 60mm / min to 100mm / min, and the ratio to the original cladding speed is ≤0.8 Powder feeding rate: 20g / min to 40g / min, powder composition is 80% to 120% of the original alloy powder After repair, use diamond grinding wheel (line speed 15m / s to 20m / s) to grind it flat and repeat the inspection steps. If the valve seat still fails after three re-inspections, it is considered scrapped.

[0049] By precisely controlling the repair parameters, the repair area can achieve good performance matching with the original cladding layer, reducing material waste and avoiding secondary damage caused by excessive processing.

[0050] 3. Passivation treatment for corrosion failure Pretreatment: Immerse the valve seat in a nitric acid solution with a mass fraction of 5% to 10%, and ultrasonically clean it for 10 to 20 minutes to remove surface impurities.

[0051] Passivation: Soak in a nitric acid solution at 40℃ to 50℃ and with a mass fraction of 5% to 10% for 10min to 20min to form a dense oxide film.

[0052] Post-treatment: rinse the valve seat surface with deionized water to remove residual acid, dry it and keep it at 200℃ to 250℃ for 0.5h to 1h to make the oxide film more stable.

[0053] Retest: After passivation, corrosion test should be repeated, and the self-corrosion current density should be ≤1×10 -6A / cm². If the requirements are met, the passivation treatment is considered qualified; otherwise, the passivation treatment needs to be repeated.

[0054] This series of performance testing, repair and passivation treatment measures form a complete closed-loop quality control system, which comprehensively improves the surface strengthening effect and service life of the polysilicon spherical control valve seat.

Claims

1. Laser cladding process for polysilicon regulating valve seat, characterized in that: The following steps are involved: Valve seat pretreatment: After using ultrasonic cleaning combined with chemical degreasing agent to remove surface oil and impurities, use aluminum oxide sand with a particle size of 0.5mm to 1mm for sandblasting to make the surface roughness reach Ra12.5μm to Ra25μm; Preparation of alloy powder: In terms of mass percentage, the alloy powder composition is 20% to 25% chromium, 10% to 15% nickel, 15% to 20% tungsten carbide particles, 3% to 5% molybdenum, 0.5% to 1% cerium, and the balance is iron; the powder particle size is controlled at 50 μm to 100 μm by a planetary ball mill, the ball milling time is 4 h to 6 h, and the ball-to-material ratio is 5:1 to 8:1; Laser cladding: using fundamental mode or low-order mode fiber laser, beam quality factor M²≤1.3, with coaxial powder feeder, multi-layer cladding on the valve seat sealing surface, laser power 1500W to 2500W, scanning speed 80mm / min to 120mm / min, spot diameter 3mm to 4mm, overlap rate 50% to 60%, each layer cladding thickness 0.3mm to 0.5mm, powder feeding amount 30g / min to 50g / min; Gradient heat treatment: Stress relief annealing: 550℃ to 650℃ for 2h to 3h; Argon protection: gas flow rate 5L / min to 10L / min, heating rate 5℃ / min to 10℃ / min, cooling rate 3°C / min to 5°C / min; Oil quenching: After keeping at 850℃ to 950℃, immerse in 40℃ to 60℃ rapid quenching oil; Staged tempering: the first stage is 200℃ to 250℃ for 1h to 1.5h, the second stage is 250℃ to 300℃ for 1h to 1.5h; Finishing: Diamond grinding wheel grinding, grinding wheel linear speed 20m / s to 30m / s, feed rate 0.01mm / r to 0.03mm / r, chemical mechanical polishing liquid polishing, polishing liquid pH value 8 to 10, pressure 0.1MPa to 0.3MPa, so that the surface roughness reaches Ra0.2μm to Ra0.4μm.

2. The laser cladding process for polysilicon regulating valve seat according to claim 1 is characterized in that: The tungsten carbide particles are spherical with an average particle size of 10 μm to 20 μm, and are uniformly dispersed in the matrix alloy by a planetary ball mill. The ball milling energy density is 0.8 J / g to 1.2 J / g, wherein the ball milling energy density is calculated by the formula E=0.5·m·v² / t, where m is the mass of the grinding ball, v is the linear velocity, and t is the time.

3. The laser cladding process for polysilicon regulating valve seat according to claim 1 is characterized in that: In the laser cladding, the laser focus position is controlled to be 0.2 mm to 0.5 mm above the valve seat surface, and the molten pool Marangoni number is less than or equal to -0.5, wherein the Marangoni number is calculated by the formula Ma=Δγ·L / μ·κ, Δγ is the surface tension gradient of the molten pool, L is the characteristic length of the molten pool, μ is the melt viscosity, κ is the thermal diffusivity, and μ and κ are in a multiplication relationship.

4. The laser cladding process for polysilicon regulating valve seat according to claim 1 is characterized in that: The residual stress of the cladding layer after the segmented tempering is ≤200MPa, and the interface bonding strength between the tungsten carbide particles and the substrate is ≥350MPa.

5. The laser cladding process for polysilicon regulating valve seat according to claim 1 is characterized in that: The planetary ball mill uses zirconium oxide grinding balls with a diameter of 5 mm to 10 mm. The inner wall of the ball mill is lined with polyurethane and the rotation speed is 200 r / min to 300 r / min.

6. The laser cladding process for polysilicon regulating valve seat according to claim 1 is characterized in that: In the alloy powder, the cerium element inhibits the oxidation of tungsten carbide through grain boundary segregation, and the cerium concentration at the grain boundary is more than 5 times that of the matrix, as measured by EDS energy spectrum.

7. A method for strengthening a polysilicon regulating valve seat, characterized in that: The following steps are also included: Step 1: Laser cladding processing: The above process is used to laser clad the valve seat sealing surface and easily worn parts to form a composite strengthening layer with a thickness of 0.9mm to 2.5mm; the molten pool morphology is monitored in real time during the cladding process to ensure that the molten pool width is 1.2 to 1.5 times the spot diameter, and there is no spatter or pores on the surface of the cladding layer; Step 2: Internal defect detection: Use ultrasonic flaw detection equipment with a frequency of 2MHz to 5MHz to scan the entire area of ​​the cladding layer. The flaw detection sensitivity is set to the base sensitivity plus 6dB, and the scanning speed is 50mm / s to 80mm / s; If the defect reflection amplitude detected exceeds 50% of the reference amplitude and the defect size is greater than 0.1mm, it is judged as unqualified; Step 3: Performance testing and grading: Hardness test: select 5 test points evenly along the circumference of the cladding layer surface and measure with Rockwell hardness tester. The surface hardness is required to be HRC55 to HRC60, and the hardness difference between adjacent test points is ≤HRC2; measure once every 0.2mm in the depth direction of the section, and the gradient difference is ≤HRC5; Wear detection: A pin-on-disc friction and wear tester is used. The wear pin is made of tungsten carbide, with a hardness of ≥HRA85 and an end surface roughness of Ra0.1μm to Ra0.2μm. The test conditions are a load of 20N to 30N, a rotation speed of 200rpm to 300rpm, and a time of 1h to 2h. After the test, the wear amount is weighed. If it is greater than 0.05g or a continuous peeling band appears on the surface, it is judged as unqualified. Corrosion test: Prepare a corrosion solution containing 10% to 15% hydrofluoric acid and 5% to 10% nitric acid by mass, and the solution temperature is 25℃±1℃; after soaking the sample for 24h, use an electrochemical workstation to test the polarization curve at a scanning rate of 0.5mV / s to 1mV / s, and the self-corrosion current density is >1×10 -6 A / cm² is considered unqualified; Step 4: Repair and re-inspection: The unqualified valve seat is partially laser remelted and repaired, and the repair area covers the 1mm to 2mm range around the defect. After repair, it is ground flat using a diamond grinding wheel at a linear speed of 15m / s to 20m / s, and steps two and three are repeated; if the valve seat still fails after three re-inspections, it is deemed scrapped.

8. The method for strengthening the valve seat of a polysilicon regulating valve according to claim 7, characterized in that: The local laser remelting repair parameters in step 4 are: The laser power is 1200W to 1800W, and the power density is a function of the thickness of the repair area, satisfying the formula: Power density = repair thickness × (500W / mm² to 800W / mm²); The scanning speed is 60mm / min to 100mm / min, and the ratio to the original cladding speed is ≤0.8; The powder feeding rate is 20g / min to 40g / min, and the powder composition is 80% to 120% of the original alloy powder.

9. The method for strengthening the valve seat of a polysilicon regulating valve according to claim 7, characterized in that: In the wear detection of step three, the contact area between the tungsten carbide pin and the valve seat is 5mm² to 10mm², and the contact pressure between the pin end face and the surface of the cladding layer is 0.5MPa to 1.0MPa; during the test, the friction coefficient is collected every 15 minutes. If the friction coefficient fluctuates by more than 0.2 or a sudden change occurs, it is determined that the cladding layer has uneven defects.

10. The method for strengthening the valve seat of a polysilicon regulating valve according to claim 7, characterized in that: If the corrosion test results in step 3 do not meet the requirements, the following passivation treatment process is used: Pretreatment: immerse the valve seat in a nitric acid solution with a mass fraction of 5% to 10%, and ultrasonically clean it for 10 to 20 minutes; Passivation: Soak in a nitric acid solution at 40°C to 50°C and with a mass fraction of 5% to 10% for 10 to 20 minutes; Post-treatment: rinse with deionized water, dry, and keep at 200℃ to 250℃ for 0.5h to 1h; Retest: After passivation, retest the corrosion test. The self-corrosion current density must be ≤1×10 -6 A / cm².

Citation Information

Patent Citations

  • Novel repair and reconstruction technique for defect treatment of strip coiler hollow axle

    CN101397663A

  • Self-lubrication abrasion-proof plunger surface and preparation method

    CN104862697A

  • Manufacturing method for intensified ball valve seat

    CN105525288A

  • Method for adopting laser cladding to repair TC4-DT titanium alloys

    CN105821408A

  • Additive repairing method for 30CrMnSiA base material adopting stainless steel powder

    CN110257825A

Cited By

  • High-stability sapphire pendulous reed processing system based on nanometer enhancement

    CN121407042A

  • Nanoparticle-enhanced high-stability sapphire pendulum processing system

    CN121407042B